2021
DOI: 10.3390/brainsci11040410
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Temporal Anodal Transcranial Direct Current Stimulation during Slow-Wave Sleep Boosts Slow-Wave Density but Not Memory Consolidation

Abstract: Slow-wave sleep (SWS) has been shown to promote long-term consolidation of episodic memories in hippocampo–neocortical networks. Previous research has aimed to modulate cortical sleep slow-waves and spindles to facilitate episodic memory consolidation. Here, we instead aimed to modulate hippocampal activity during slow-wave sleep using transcranial direct current stimulation in 18 healthy humans. A pair-associate episodic memory task was used to evaluate sleep-dependent memory consolidation with face–occupatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Slow oscillatory tDCS (so-tDCS) studies have been conducted based on this hypothesis. However, some recent studies have indicated that so-tDCS does not improve memory consolidation despite increasing SWA and spindle activity [66][67][68][69]; however, any definite conclusions could be controversial and there is therefore a need for further refinement [70,71]. Saebipour et al [65] conducted a study of the application of so-tDCS (0.75 Hz) with an intensity ranging from 0 to 260 μA during stage 2 of NREM sleep in six patients with either sleep maintenance or non-restorative sleep insomnia with the goal of resonating their brain waves to the frequency of sleep slow-wave.…”
Section: Transcranial Direct Current Stimulation and Slow Wave Activitymentioning
confidence: 99%
“…Slow oscillatory tDCS (so-tDCS) studies have been conducted based on this hypothesis. However, some recent studies have indicated that so-tDCS does not improve memory consolidation despite increasing SWA and spindle activity [66][67][68][69]; however, any definite conclusions could be controversial and there is therefore a need for further refinement [70,71]. Saebipour et al [65] conducted a study of the application of so-tDCS (0.75 Hz) with an intensity ranging from 0 to 260 μA during stage 2 of NREM sleep in six patients with either sleep maintenance or non-restorative sleep insomnia with the goal of resonating their brain waves to the frequency of sleep slow-wave.…”
Section: Transcranial Direct Current Stimulation and Slow Wave Activitymentioning
confidence: 99%
“…In the supnoise condition, no eyes-open periods were introduced. The participants were not aware of the purpose of this study (i.e., the comparison of three resting-state EEG recordings with different conditions), as the data for the current study were recorded preceding the data acquisition of the study Ruch et al ( 2021 ), which involved several EEG recordings and lying in the MRI simulator. This circumstance led to the study design limitation, namely a fixed order of the posture and ASN setting as described above, without counterbalance.…”
Section: Methodsmentioning
confidence: 99%
“…The EEG recording setup was the same as in Ruch et al ( 2021 ), with 22 sintered chloride ring electrodes mounted on an elastic cap and complying with the international 10–20 system (Fp1, Fp2, F3, F4, C3, C4, P3, P4, O1, O2, F7, F8, FT9, FT10, T5, T6, Fz, Cz, Pz, Oz, CP5, CP6). Cz was the recording reference and the ground electrode was located between Pz and Oz.…”
Section: Methodsmentioning
confidence: 99%
“…Although several studies consistently showed that it is possible entraining and boosting NREM slow oscillations and/or spindles using rhythmic or closed loop acoustic, tactile or electrical stimulations (e.g., Henin et al, 2019;Navarrete et al, 2020;Pereira et al, 2017;Ruch et al, 2021;Simor et al, 2018), it is less clear how and to what extent boosting slow oscillations or spindles during post-training sleep benefits memory consolidation, and several studies concluded null effects (e.g., Henin et al, 2019;Pereira et al, 2017;Ruch et al, 2021).…”
Section: Can We Modulate Previously Learned Information During Sleep?...mentioning
confidence: 99%
“…Finally, an even more recently emerging paradigm is the ongoing stimulation of sleep oscillations by external sensory stimulations. Although several studies consistently showed that it is possible entraining and boosting NREM slow oscillations and/or spindles using rhythmic or closed loop acoustic, tactile or electrical stimulations (e.g., Henin et al, 2019; Navarrete et al, 2020; Pereira et al, 2017; Ruch et al, 2021; Simor et al, 2018), it is less clear how and to what extent boosting slow oscillations or spindles during post‐training sleep benefits memory consolidation, and several studies concluded null effects (e.g., Henin et al, 2019; Pereira et al, 2017; Ruch et al, 2021). Still, a meta‐analysis conducted over 11 experiments found that acoustic enhancement of slow wave sleep indeed tends to increase the overnight consolidation of episodic memory, but with only small and at trend level effects (Wunderlin et al, 2021).…”
Section: Recent Advances In Information Processing Learning and Memor...mentioning
confidence: 99%